Raymond Hide. 17 May 1929—6 September 2016. (21st December 2019) - Read, P. L.
Abstract : Raymond Hide was a physicist who worked at the interfaces between fundamental hydrodynamics, magnetohydrodynamics (MHD), the geophysics of the Earth's interior, atmosphere and oceans and those of other planets. He received his PhD from the University of Cambridge, and spent the majority of his career at the Met Office and then the University of Oxford. In laboratory studies of sloping thermal convection carried out at Cambridge in the early 1950s he discovered various regimes of vacillation and other multiply-periodic intransitive flows as well as aperiodic flows, now recognized as a form of geostrophic turbulence. These findings influenced seminal mathematical studies of what came to be known as deterministic chaos, and provided a paradigm for interpreting large-scale flows in the atmospheres of the Earth and other planets. Related contributions include general theoretical results tested by crucial laboratory experiments on boundary layers, Taylor columns and detached shear layers. His contributions to MHD include the concepts of potential magnetic field and magnetic superhelicity. He also initiated research on the dynamo origin of the magnetic fields of Jupiter and other major planets and its implications for their internal structure and dynamics. His extensive research on fluctuations of the Earth's rotation led to new developments in areas as diverse as meteorology and climatology and studies of the structure and dynamics of the Earth's deep interior.